Implementasi IoT sebagai Solusi Inovatif Peningkatan Produktivitas dan Manajemen UMKM Ukir Furnicraft Jepara - Sa'diyah, Mahmudatus; Arifin, Zaenal; Ulfah, Sofia; Pambudi, Fivin Bagus Septiya; Rizky, Dimas Ahmad; Amanda, Pingkan Nova (Abdimas Universal, 2026)
Jepara’s woodcarving industry is one of the leading SME sectors that faces significant challenges in the era of Industry 4.0, particularly regarding limited production capacity, manual financial management, and insufficient human resource skills. The partner, Ajining Furniture, still relies on traditional tools, often leading to delays in production and unstructured administrative records. This study aims to enhance productivity and competitiveness through the adoption of Internet of Things (IoT) technology in the CNC Mach 6090 machine and the development of web- and mobile-based digital applications for financial reporting and invoicing. A participatory approach was employed through stages of socialization, training, mentoring, technology implementation, and evaluation. The results indicate an increase in production capacity from 100 pcs/day to 180 pcs/day, improved carving quality with higher precision, and a significant transformation in financial and administrative management toward more structured and professional practices. Furthermore, the partner gained new knowledge of IoT technology, supporting adaptation to modern industrial demands. Thus, IoT adoption has proven effective in strengthening production capacity, managerial efficiency, and the competitiveness of Jepara’s woodcarving industry.